(untitled) (Academicia Globe: Inderscience Research, 2023)
A birth defect is something visibly abnormal, internally abnormal, or chemically abnormal about your newborn baby’s body. The defect might be caused by genetics, infection, radiation, or drug exposure, or there might be no known reason. Examples of birth defects include phenylketonuria, sickle cell anemia and Down syndrome.